(3GdGSdGehjI h GdMOGKI (B:s (3GdNWGH GdeJZjQ aj GjQGf (B/s - (3QLGFj, aQgfc, (B1952-s ((3GHh XHj (B:s (3eQcR GdEeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjI(B,s, 2010)
(3GdLjd GdGhd (B: (3SjGSGJ GdGMjGA, ef GdYTQjfGJ Gdi GdSJjfGJ (B-- (3GdLjd GdKGfj(B: (3SjGSGJ GdKhQI, (B1963-1991 -- (3GdLjd GdKGdK (B: (3SjGSGJ GdGSdGehjI, (B1989-1997 -- (3GdLjd GdQGHY (B: (3SjGSGJ GdGSJYGOI, (B1997-2005 -- (3GdNGJeI (B: (3SjGSGJ GdJCQLMs
(3OQGSGJ eJQLeI; (B42s
Keywords: (3GdGSdGe (B-- (3GjQGf (B-- (3JGQjNs; (3GdGSdGe h GdOhdI (B-- (3GjQGfs; (3GjQGf (B-- (3SjGSI h McheI (B-- 20(3GdbQfs; (3GjQGf (B-- (3SjGSI h McheI (B-- 21(3GdbQfeQcR GdEeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjIs